Unobstructed Ultrathin Gas Transport Channels in Composite Membranes by Interfacial Self‐Assembly. Issue 22 (24th April 2020) - Wang, Bo; Qiao, Zhihua; Xu, Jiayou; Wang, Jixiao; Liu, Xinlei; Zhao, Song; Wang, Zhi; Guiver, Michael D.
Abstract: Ultrathin unobstructed gas transport channels through the membrane selective layer are constructed in mixed matrix membranes (MMMs) by using gravity‐induced interface self‐assembly of poly(vinylamine) and polymer‐modified MIL‐101(Cr). For CO2 /N2 (15/85 by volume) mixed gas, the MMMs achieve a high CO2 permeance of 823 gas permeation units and CO2 /N2 selectivity of 242 at 0.5 MPa. Based on economic analyses, a two‐stage membrane process can achieve gas separation and economic targets. Abstract : Ultrathin unobstructed gas transport channels through the membrane selective layer are constructed in mixed matrix membranes (MMMs) by using gravity‐induced interface self‐assembly of poly(vinylamine) and polymer‐modified MIL‐101(Cr). For CO2 /N2 (15/85 by volume) mixed gas, the MMMs achieved a high CO2 permeance of 823 gas permeation units and CO2 /N2 selectivity of 242 at 0.5 MPa.